IMPLEMENTASI MODUL ILO SCORE DI KERIPIK ANEN KHAS BENGKAYANG - Deri, Kristianus Natanael; Sugianto, Helena Anggraeni (Reni) Tjondro (Jurnal Pengabdian Bukit Pengharapan, 2024)
The community service held by the Shanti Bhuana Institute aims to motivate MSMEs so they can compete in the increasingly growing era of globalization. The service carried out by the Shanti Bhuana Institute academics was carried out in three stages, namely the observation and preparation method, implementation or implementation of the ILO SCORE module, and evaluation. The method of implementing this service is training, practice. This service was carried out at one of the MSMEs in Bengkayang Regency, namely the Anen Bengkayang Chips Shop. The service directly involves the owner of the Anen Bengkayang Chips Shop. Based on the results of the service, it appears that the Anen Chips Shop has become more neat and clean, making consumers comfortable and increasing the number of consumers who come to the shop. The aim of the service is to provide understanding and insight to the Anen Bengkayang Chips Shop Owner regarding ILO SCORE Module Based management, planning and implementing the modules in ILO SCORE for the Bengkayang Anen Chips Shop. The methods used in the ILO SCORE module are 5S, and Hygine. The results of the activity have been successful in implementing the 5S Layout Module, for product layout and Hygine.